The Role of Student Independent Work in The Educational Process (Diversity Research: Journal of Analysis and Trends, 2023)
The organization of independent work of students of higher education is one of the topical issues and requires great experience and skill from the teacher. The subject "Information technologies in education" occupies a special place in the areas of teacher education, being inextricably linked with other subjects. The organization of independent work of students in science has its own characteristics. It is these features and the solution of the problems arising from this that the main attention is paid to in the article.